Respuesta :

Answer:

[tex]x = 7[/tex]

[tex]y = - 6[/tex]

Step-by-step explanation:

Add 4y to both sides in the first equation:

[tex]x = 31 + 4y[/tex]

Substitute that new equation into the second equation:

[tex] - (31 + 4y) + 3y = - 25[/tex]

[tex] - 31 - 4y + 3y = - 25[/tex]

[tex] - 31 - y = - 25[/tex]

Add 31 to both sides:

[tex] - y = 6[/tex]

Divide -1 on both sides:

[tex]y = - 6[/tex]

Substitute y=-6 in the third equation (first equation but modified)

[tex]x = 31 + 4y[/tex]

[tex]x = 31 + 4 ( - 6)[/tex]

[tex]x = 31 + ( - 24)[/tex]

[tex]x = 31 - 24[/tex]

[tex]x = 7[/tex]

ACCESS MORE